2006
DOI: 10.1159/000090388
|View full text |Cite
|
Sign up to set email alerts
|

Encasement of Bedding Does Not Improve Asthma in Atopic Adult Asthmatics

Abstract: Aim: We evaluated the impact of impermeable bed covers on asthma in asthmatics with clinically relevant house dust mite (HDM) sensitization. Methods: The study included 32 HDM-sensitized asthmatics in whom HDM allergy was considered as a significant factor in their asthma. They were randomized into either an intervention group whose bedding was encased with impermeable covers, or a control group who received cotton covers. Before and 3 and 6 months after encasement, dust samples were collected from the bedding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…This is highlighted by the findings of WOODCOCK et al [80], which showed that allergen-impermeable covers as a single intervention in the avoidance of exposure to HDM allergen were clinically ineffective in adult asthmatics. The current authors have found similar negative findings in a HDM avoidance study directed specifically at patients in whom HDM was clinically relevant [81].…”
Section: Bronchoscopic Assessment Of Interventions In Human Diseasesupporting
confidence: 81%
“…This is highlighted by the findings of WOODCOCK et al [80], which showed that allergen-impermeable covers as a single intervention in the avoidance of exposure to HDM allergen were clinically ineffective in adult asthmatics. The current authors have found similar negative findings in a HDM avoidance study directed specifically at patients in whom HDM was clinically relevant [81].…”
Section: Bronchoscopic Assessment Of Interventions In Human Diseasesupporting
confidence: 81%
“…It was evident from this study that the nonwoven fabrics will allow surface penetration, and in some cases they appeared to allow colonization. Additionally, it was observed that normal use of fabrics made this more likely, as shown in Fig 2. Although clinical recommendations for use of encasings remains controversial, [15][16][17] at least in terms of primary prevention of allergies, it is clear that the materials used to construct covers have not been adequately considered, and the design in some cases remains suboptimal. Ideally, such covers should both provide comfort by allowing transfer of air and moisture, as well as preventing the passage of allergens and the colonization by mites.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no experimental, non-clinical study has evaluated the structural integrity of tightly woven covers for withstanding mite and allergen penetration after repeated washings and use over a long period of time. However, a number of studies have recorded allergen decrements as a result of impermeable encasements alone after nine weeks [5], six months [27,28], and one year [22,23], which suggests that the structural integrity of these encasements was not compromised.…”
Section: Discussionmentioning
confidence: 99%